2021
DOI: 10.3389/fimmu.2021.732690
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 (ACE2) in the Pathogenesis of ARDS in COVID-19

Abstract: Seventeen years after the epidemic of SARS coronavirus, a novel coronavirus SARS-CoV-2-emerged resulting in an unprecedented pandemic. Angiotensin-converting enzyme 2 (ACE2) is an essential receptor for cell entry of SARS-CoV-2 as well as the SARS coronavirus. Despite many similarities to SARS coronavirus, SARS-CoV-2 exhibits a higher affinity to ACE2 and shows higher infectivity and transmissibility, resulting in explosive increase of infected people and COVID-19 patients. Emergence of the variants harboring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 34 publications
0
39
0
2
Order By: Relevance
“…S binds to angiotensin-converting enzyme 2 (ACE2), which is highly expressed on type II alveolar lung epithelium (Hamming et al , 2004; Zhao et al , 2020), triggering conformational changes that facilitate fusion of the viral envelope and host cell membrane (Huang et al , 2020). ACE2 is a protease of the renin-angiotensin-aldosterone system (RAAS), which catalyzes the cleavage and inactivation of the vasoconstrictor angiotensin II (Ang-II) (Vickers et al , 2002; Tipnis et al , 2000), as well as the cleavage of other pro-inflammatory peptides in the kinin system that promote vascular leakage (Vickers et al , 2002), and formation of Ang 1-7 to mediate anti-inflammation, anti-fibrosis, and vasodilation through Mas signaling (Kuba et al , 2021; Santos et al , 2003). The extracellular domains of ACE2 can be expressed as a soluble protein (sACE2) that blocks the RBD (Hofmann et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…S binds to angiotensin-converting enzyme 2 (ACE2), which is highly expressed on type II alveolar lung epithelium (Hamming et al , 2004; Zhao et al , 2020), triggering conformational changes that facilitate fusion of the viral envelope and host cell membrane (Huang et al , 2020). ACE2 is a protease of the renin-angiotensin-aldosterone system (RAAS), which catalyzes the cleavage and inactivation of the vasoconstrictor angiotensin II (Ang-II) (Vickers et al , 2002; Tipnis et al , 2000), as well as the cleavage of other pro-inflammatory peptides in the kinin system that promote vascular leakage (Vickers et al , 2002), and formation of Ang 1-7 to mediate anti-inflammation, anti-fibrosis, and vasodilation through Mas signaling (Kuba et al , 2021; Santos et al , 2003). The extracellular domains of ACE2 can be expressed as a soluble protein (sACE2) that blocks the RBD (Hofmann et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since increased Ang II and imbalance between AT1R and Mas receptor signals are involved in the pathogenesis of ARDS, ACE2 which converts Ang II to Ang 1–7, is expected to resolve this imbalance and improve lung inflammatory injury [ 29 , 30 ]. Indeed, the development of rhACE2 was motivated by its therapeutic effect in animal models of ARDS [ 31 ]. In clinical studies, although rhACE2 was well-tolerated in both healthy human volunteers and ARDS patients, and treatment resulted in rapid conversion of Ang II to Ang 1–7, no beneficial changes in acute physiology or clinical outcomes was detected [ 28 , 32 ].…”
Section: Ace2 As An Enzymatic Drug For Ards and Decoy Receptor For Co...mentioning
confidence: 99%
“…Considering the therapeutic potential of rhACE2 for ARDS via conversion of proinflammatory Ang II to Ang 1–7, the enzymatic activity of the ACE2 decoy is expected to ameliorate lung inflammatory injury due to SARS-CoV-2 infection. Although there is extensive evidence to support the efficacy of rhACE2 in animal models of ARDS [ 30 , 31 ], Phase 2 trials have found no improvement in clinical outcomes of ventilated ARDS patients. It is possible that the dosage of rhACE2 may have been insufficient to show beneficial effects [ 30 ].…”
Section: Dual Aspects Of Ace2 Enzymatic Activity On Drugs For Covid-19mentioning
confidence: 99%
“…Moreover, the dysregulation in ACE2 expression in lung tissue may exacerbate outcomes in COVID-19 patients ( 70 ). In COVID-19 patients, ACE2 expression and the WNT/β-catenin pathway appeared to be interrelated ( 18 ).…”
Section: Hypothesis Of Cbd and Wnt/β-catenin Pathway In Sars-cov-2mentioning
confidence: 99%